An interactive environment for solid modeling based on free software - Moraes, H. P.; Machado, J. M.; Verardi, SLL; Cardoso, JR; Yan, W.; Wang, Z. M. (World Publishing Corporation, 2000)
This paper describes an interactive environment built entirely upon public domain or free software, intended to be used as the preprocessor of a finite element package for the simulation of three-dimensional electromagnetic problems.
Keywords: finite element preprocessing; Graphical User Interfaces; software methodology; solid modeling